Molecular characterization of the permanent outer-inner membrane contact site of the mitochondrial genome segregation complex in trypanosomes. - Philip Stettler; Bernd Schimanski; Salome Aeschlimann; André Schneider (PLoS Pathogens)
The parasitic protozoan Trypanosoma brucei has a single unit mitochondrial genome linked to the basal body of the flagellum via the tripartite attachment complex (TAC). The TAC is crucial for mitochondrial genome segregation during cytokinesis. At the core of the TAC, the outer membrane protein TAC60 binds to the inner membrane protein p166, forming a permanent contact site between the two membranes. Although contact sites between mitochondrial membranes are common and serve various functions, their molecular architecture remains largely unknown. This study elucidates the interaction interface of the TAC60-p166 contact site. Using in silico, in vitro, and mutational in vivo analyses, we identified minimal binding segments between TAC60 and p166. The p166 binding site in TAC60 consists of a short kinked α-helix that interacts with the C-terminal α-helix of p166. Despite the presence of conserved charged residues in either protein, electrostatic interactions are not necessary for contact site formation. Instead, the TAC60-p166 interaction is driven by the hydrophobic effect, as converting conserved hydrophobic residues in either protein to hydrophilic amino acids disrupts the contact site.